2021
DOI: 10.1002/tsm2.280
|View full text |Cite
|
Sign up to set email alerts
|

Tendon blood flow, angiogenesis, and tendinopathy pathogenesis

Abstract: Physical exercise results in a duration and intensity‐dependent vascular response in healthy human tendon. In overused (tendinopathy) and damaged tendon, angiogenic pathways are activated and neovascularization is observed. Whereas no direct relationship exists between the amount of neovessels and degree of tendinopathy symptoms, almost all tendinopathic patients have elevated neovascularization and tendon blood flow, as assessed by Doppler ultrasound methodology. The enhanced flow in tendinopathy can be succe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 154 publications
0
3
0
3
Order By: Relevance
“…Die langsame Übungsdurchführung mit hohem Gewicht übt einen großen Reiz auf die extrazellu-läre Matrix aus, die wiederum über verschiedene Signalwege die Tenozyten zur Kollagenproduktion anregt [5], [19]. Zudem gibt es Hinweise, dass die reduzierte Durchblutung der insuffizienten Neovaskularisierung während der Übungsdurchführung positive Effekte auf die Heilung hat [7], [21], [22], [23]. Auch ein positiver Einfluss der genannten Trainingsform auf die neuromuskuläre Aktivierung wird diskutiert [24].…”
Section: Risikofaktorenunclassified
“…Die langsame Übungsdurchführung mit hohem Gewicht übt einen großen Reiz auf die extrazellu-läre Matrix aus, die wiederum über verschiedene Signalwege die Tenozyten zur Kollagenproduktion anregt [5], [19]. Zudem gibt es Hinweise, dass die reduzierte Durchblutung der insuffizienten Neovaskularisierung während der Übungsdurchführung positive Effekte auf die Heilung hat [7], [21], [22], [23]. Auch ein positiver Einfluss der genannten Trainingsform auf die neuromuskuläre Aktivierung wird diskutiert [24].…”
Section: Risikofaktorenunclassified
“…52 53 In addition to these neovessels, tendinopathy samples have been shown to have higher levels of several neurochemicals directly associated with pain including glutamate, substance P and lactate. [54][55][56] The significance of these neurotransmitters remains unclear, but in addition to promoting angiogenesis, these may be triggering a 'neuropathictype' pain by stimulation of the local nerve endings, as it is thought that the development of neovascularity may also be associated with the ingrowth of abnormal sensory nerve endings into tendinopathic tendons. [57][58][59][60] This concept of neoneuralisation has not been explored in as much detail as the presence of neovascularisation, but this could potentially be a direct source of (neural) pain in patients with tendinopathies.…”
Section: What This Study Addsmentioning
confidence: 99%
“…Although several studies in recent years have identified that while this ingrowth of blood vessels may be common, its precise function remains unclear; and while hypotheses suggest these may be related to tendon hypoxia,48 their presence poorly correlates with symptoms49–51 and neovessels are not necessarily changed by treatments 52 53. In addition to these neovessels, tendinopathy samples have been shown to have higher levels of several neurochemicals directly associated with pain including glutamate, substance P and lactate 54–56. The significance of these neurotransmitters remains unclear, but in addition to promoting angiogenesis, these may be triggering a ‘neuropathic-type’ pain by stimulation of the local nerve endings, as it is thought that the development of neovascularity may also be associated with the ingrowth of abnormal sensory nerve endings into tendinopathic tendons 57–60.…”
Section: Introductionmentioning
confidence: 99%
“…Die langsame Übungsdurchführung mit hohem Gewicht übt einen großen Reiz auf die extrazelluläre Matrix aus, die wiederum über verschiedene Signalwege die Tenozyten zur Kollagenproduktion anregt[5,19]. Zudem gibt es Hinweise, dass die reduzierte Durchblutung der insuffizienten Neovaskularisierung während der Übungsdurchführung positive Effekte auf die Heilung hat[7,[21][22][23]. Auch ein positiver Einfluss der genannten Trainingsform auf die neuromuskuläre Aktivierung wird diskutiert…”
unclassified